Implikasi Program Pelatihan Berbasis Ekonomi Kemasyarakatan Di Desa Bajo Kabupaten Boalemo - Fibriyanti S. Lakoro; Sukrianto (Yayasan Literasi Sains Indonesia, 2022)
The purpose of the study was to determine the type of program that is good in improving the community economy, especially economic-based development in Bajo Village. To find out the impact of a training program that does not go well. Finally, to find out the impact of the community-based economic training program in Bajo Village. The research method described in this study is a qualitative approach. The data analysis technique used using the Miles and Huberman model is data reduction, data presentation, and drawing conclusions. The results of the study can be explained that the implications of the Community Economic-Based Training Program in Bajo Village, Boalemo Regency are considered to be still not good due to the lack of capital needed by the community in business groups or individuals. In addition, the level of public awareness in carrying out the training program is considered not going well. Many things, like most people, are more focused on searching the sea or fishing. In addition, the community does not have the understanding and knowledge in carrying out entrepreneurship-based activities. Many people think that the results of managed products are only profitable for the community itself. Even the lack of marketing in running the business that is run.